2022
DOI: 10.18844/wjet.v14i3.7366
|View full text |Cite
|
Sign up to set email alerts
|

Student-centered technology in the professional training of future biology teachers for the regional component

Abstract: One of the most pressing global problems today is the prevention of environmental crises is achieved only through targeted actions of people. In this regard, the search for ways out of the environmental crisis is being carried out, which is reflected in the laws "On environmental protection of the Republic of Kazakhstan", "Emergencies of natural and technogenic character ", as well as in state documents dedicated to environmental issues. as the "National Action Plan for Environmental Protection for Sustainable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The result indicated that students' attitudes towards the implementation of PBL was positive. It was beneficial in improving student's writing ability and their awareness of environmental issues (Azhmoldaeva, Zharylkasynovna, Shildebayev, Zhunisov, Azhibaevna & Ganievna, 2022).…”
Section: Previous Research On Pblmentioning
confidence: 99%
“…The result indicated that students' attitudes towards the implementation of PBL was positive. It was beneficial in improving student's writing ability and their awareness of environmental issues (Azhmoldaeva, Zharylkasynovna, Shildebayev, Zhunisov, Azhibaevna & Ganievna, 2022).…”
Section: Previous Research On Pblmentioning
confidence: 99%
“…The result indicated that students' attitudes towards the implementation of PBL was positive. It was beneficial in improving student's writing ability and their awareness of environmental issues (Azhmoldaeva, Zharylkasynovna, Shildebayev, Zhunisov, Azhibaevna & Ganievna, 2022).…”
Section: Previous Research On Pblmentioning
confidence: 99%